1999
DOI: 10.1210/jcem.84.12.6197
|View full text |Cite
|
Sign up to set email alerts
|

Tension Pneumocranium, a Rare Complication of Transsphenoidal Pituitary Surgery: Mayo Clinic Experience 1976–1998

Abstract: We describe four cases of symptomatic pneumocranium, a rare, potentially life-threatening complication of transsphenoidal pituitary surgery. Symptomatic pneumocranium manifested as impaired mental status, headaches, and grand mal seizures, early in the postoperative course after transsphenoidal pituitary surgery. Furthermore, a Cushing response, including systemic hypertension and bradycardia (secondary to intracranial hypertension) was seen, which has not been previously described in association with symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…According to our peroperative protocol, the ELD was removed on the fifth day in most patients, which may explain why we did not observe any lumbar catheterrelated infections. Symptomatic pneumocephalus due to lumbar CSF-drainage is another rare, life-threatening complication, which did not occur in the present series [25,26].…”
Section: Discussionmentioning
confidence: 89%
“…According to our peroperative protocol, the ELD was removed on the fifth day in most patients, which may explain why we did not observe any lumbar catheterrelated infections. Symptomatic pneumocephalus due to lumbar CSF-drainage is another rare, life-threatening complication, which did not occur in the present series [25,26].…”
Section: Discussionmentioning
confidence: 89%
“…A study conducted in guinea pigs demonstrated that elevating MEP with air up to 250 daPa had no effect on auditory thresholds measured by auditory brainstem response (ABR) [8]. While it appears that hearing is likely not significantly affected in most individuals, there have been rare reports of tympanic membrane rupture, pneumocephalus, and tension pneumocranium with CPAP use [9][10][11][12]. Although rare, these findings should prompt caution with CPAP use following head trauma, rhinologic or otologic surgery, and particularly following intradural skull base procedures.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another, but rare, complication of postoperative CSF leak following TSS is tension pneumocephalus. 27 Meticulous closure of the sellar defect has been advocated to prevent complications. Unfortunately, a limited working space and complex anatomy of the sinuses have resulted in marginal success.…”
Section: Discussionmentioning
confidence: 99%